2022
DOI: 10.1155/2022/4154440
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Suppresses Osteogenic Differentiation of Rat Bone Marrow-Derived Mesenchymal Stem Cells via AKT/GSK-3β/β-Catenin Signaling Pathway

Abstract: Nervous system is critically involved in bone homeostasis and osteogenesis. Dopamine, a pivotal neurotransmitter, plays a crucial role in sympathetic regulation, hormone secretion, immune activation, and blood pressure regulation. However, the role of dopamine on osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (rBMSCs) remains poorly understood. In this study, we firstly investigated the effect of dopamine on the apoptosis, proliferation, and osteogenic differentiation of rBMSCs. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This is consistent with previous results reported in HeLa cells [10]. ALP activity, expression of RUNX2, Osterix, OCN, and calcified nodules detected by Alizarin red are generally regarded as osteogenic related differentiation markers [18]. They are vastly used to assess osteogenic capability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous results reported in HeLa cells [10]. ALP activity, expression of RUNX2, Osterix, OCN, and calcified nodules detected by Alizarin red are generally regarded as osteogenic related differentiation markers [18]. They are vastly used to assess osteogenic capability.…”
Section: Discussionsupporting
confidence: 91%
“…Western Blot Analysis. Western blot was performed as described before [18]. Total proteins were extracted from the cells by RIPA lysis buffer (Beyotime, China) with 1% protease inhibitor (CoWin Biosciences, China).…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%
“…A recent study by Hong and colleagues supported these findings. They found that dopamine did not interfere with the apoptosis and proliferation of rBMSCs (rat bone marrow mesenchymal stromal cells) at a concentration of 10 μM, but inhibited osteogenic differentiation of rBMSCs through the AKT/GSK-3β/β-Catenin signaling pathway, reduced ALP activity and minimized nodule formation, and decreased expression of osteogenic associated genes ( Col1a1, ALP, Runx2, Opn, and Ocn ) [ 58 ]. These studies indicated that different dopamine concentrations might cause different results in osteogenic differentiation of BMSC.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Because of the formation of these nerve endings, OA is a chronic pain condition; however, the role of neurotransmitters during OA is just beginning to be understood [ 139 , 140 , 141 , 142 , 143 , 144 ]. Although cartilage lacks nerve endings, chondrocytes have been found to express some catecholamine receptors, and the role of DA during bone formation has been studied in vitro and also in fracture models in adult individuals [ 140 , 145 , 146 ]. Another important aspect in the pathogenesis of OA is inflammation, which is exacerbated in the initial phase of OA, mainly by cytokines such as interleukin-1β (IL-1β) and tumor necrosis factor alpha (TNFα), which can also contribute to the damage of articular chondrocytes and ultimately to the dedifferentiation of chondrocytes to a fibrocartilaginous phenotype and finally to bone formation [ 144 , 147 , 148 , 149 ].…”
Section: Therapeutic Potential Of Dopamine (Da) and Dopamine Agonists...mentioning
confidence: 99%